Knowledge, attitude and perception of African immigrants in South Africa to Covid-19 vaccination - Ohiagu, Shedrach (Department of Medicine, 2025)
Background: The COVID-19 pandemic has posed unprecedented challenges globally. Vaccination has emerged as a crucial tool in mitigating the impact of the virus. However, the success of vaccination campaigns depends largely on public acceptance and uptake. This study aimed to assess the knowledge, attitudes, and perceptions of African immigrant participants towards the COVID-19 vaccine. Methods: The study was a cross-sectional descriptive study in which a close-ended validated questionnaire was used to collect data from 202 participants from a periurban area of Cape Town. Participants were presented with a series of questions assessing their knowledge, attitudes, and perceptions towards the COVID-19 vaccine. Responses were scored and categorised to evaluate the participants' understanding and acceptance of the vaccine. Results: The study included 202 participants with a mean age of 31.6 years, ranging from 18 to 80 years. The majority (42.5%) fell within the 26-33 years age group, and 65% were aged 33 or younger. Males constituted 60% of the participants, and about half (49.5%) were born in Zimbabwe. A significant portion (68.53%) had not experienced COVID-19 symptoms, while 47% had not received any COVID-19 vaccination at the time of the research. With regards to the overall knowledge of the COVID-19 vaccine, 24.26% have poor knowledge, 46.04% have fair knowledge, and 29.70% have good knowledge. With regards to overall attitude, 59% have a negative attitude, and 41% have a positive attitude. For the overall perception, 52% have a negative perception and 48% a positive perception. Conclusion: These findings underscore the complexity of vaccine acceptance and highlight the need for multifaceted strategies to improve vaccine uptake. These could include educational interventions to address knowledge gaps and misconceptions, as well as strategies to leverage social influence and address attitudinal barriers to vaccination. Further research is needed to explore these factors in more depth and develop effective interventions for improving vaccine acceptance and uptake among this population.